2016
DOI: 10.11114/jets.v4i12.1977
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between the Fourth Grade Students’ Level of Functional Literacy and Metacognitive Awareness

Abstract: The present study aims at presenting the relationship between the fourth grade primary school students' level of functional literacy and metacognitive awareness. The study group of the research is made up of 406 fourth grade students attending school during 2015-2016 academic year in Niğde. This study adopts survey model and its data collection tools include the Functional Literacy Experience Scale based upon Ecological Theory (FLESBUET) and the Metacognitive Awareness Scale for Children. In relation to these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Sümen and Çalışıcı (2016) found a significant relationship amongst teacher candidates' problem-solving skills, metacognitive awareness, and mathematics literacy. Özenç and Dikici (2016) revealed a moderate and positive relationship between 4th grade students' literacy levels and their metacognitive awareness. Metacognition enables the problem solver to strategically code the problem, develop a mental scheme, choose and plan an appropriate strategy to achieve the goal, and recognize and overcome challenges along the way.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 90%
See 2 more Smart Citations
“…Sümen and Çalışıcı (2016) found a significant relationship amongst teacher candidates' problem-solving skills, metacognitive awareness, and mathematics literacy. Özenç and Dikici (2016) revealed a moderate and positive relationship between 4th grade students' literacy levels and their metacognitive awareness. Metacognition enables the problem solver to strategically code the problem, develop a mental scheme, choose and plan an appropriate strategy to achieve the goal, and recognize and overcome challenges along the way.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 90%
“…In her study, Özenç (2012) found functional literacy of 4th and 5th grade students at medium level. Again, Özenç and Dikici (2016) revealed that 4th grade students' functional literacy was medium. Unlike these studies, Glušac, Pilipovic, and Milic (2020) determined that the functional literacy of 3rd grade secondary school students was at a disturbing level.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The characteristics of metacognition are realizing that the solution strategy is not right but not improving it, planning the strategy that is made but not realizing the accuracy of the strategy, not showing monitoring activities and not sure what is being thought and tends to not master the concept. For the functional literacy group, the use of metacognition leads to awareness of their knowledge but still has difficulty connecting some related mathematical concepts (Ali et al, 2020;Özenç & Dikici, 2016;Zhussupova & Kazbekova, 2016). In the use of metacognition activities, the characteristics that are raised are being aware of what is thinking, planning various strategies consciously to increase the accuracy of his thinking, but not always using these strategies, tending to monitor his thinking processes, showing a tendency to master the mathematical concepts underlying the problem.…”
Section: Discussionmentioning
confidence: 99%